Axially bound magnetic skyrmions: glueing topological strings across an interface - Ran, K; Liu, Y; Jin, H; Shangguan, Y; Guang, Y; Wen, J; Yu, G; van der Laan, G; Hesjedal, T; Zhang, S (American Chemical Society, 2022)
A major challenge in topological magnetism lies in the three-dimensional (3D) exploration of their magnetic textures. A recent focus has been the question of how 2D skyrmion sheets vertically stack to form distinct types of 3D topological strings. Being able to manipulate the vertical coupling should therefore provide a route to the engineering of topological states. Here, we present a new type of axially bound magnetic skyrmion string state in which the strings in two distinct materials are glued together across their interface. Using quasi-tomographic resonant elastic x-ray scattering, the 3D skyrmion profiles before and after their binding across the interface were unambiguously determined and compared. Their attractive binding is accompanied by repulsive twisting, i.e., the coupled skyrmions mutually affect each other via a compensating twisting. This state exists in chiral magnet-magnetic thin film heterostructures, providing a new arena for the engineering of 3D topological phases.